Shining a Light on Awareness: A Review of Functional Near-Infrared Spectroscopy for Prolonged Disorders of Consciousness - Rupawala, Mohammed; Dehghani, Hamid; Lucas, Samuel J. E.; Tino, Peter; Cruse, Damian (Frontiers in Neurology, 2018)
Qualitative clinical assessments of the recovery of awareness after severe brain injury require an assessor to differentiate purposeful behaviour from spontaneous behaviour. As many such behaviours are minimal and inconsistent, behavioural assessments are susceptible to diagnostic errors. Advanced neuroimaging tools can bypass behavioural responsiveness and reveal evidence of covert awareness and cognition within the brains of some patients, thus providing a means for more accurate diagnoses, more accurate prognoses, and, in some instances, facilitated communication. The majority of reports to date have employed the neuroimaging methods of functional magnetic resonance imaging, positron emission tomography, and electroencephalography (EEG). However, each neuroimaging method has its own advantages and disadvantages (e.g. signal resolution, accessibility, etc.). Here, we describe a burgeoning technique of non-invasive optical neuroimaging – functional near-infrared spectroscopy (fNIRS) – and review its potential to address the clinical challenges of prolonged disorders of consciousness. We also outline the potential for simultaneously-acquired EEG to complement the fNIRS signal, and suggest the future directions of research that are required in order to realise its clinical potential.